Diagnosis, prognostic prediction of the accelerated phase of chronic lymphocytic leukaemia: a narrative review - Michalak, Krzysztof; Mazur, Łukasz; Bujara, Alicja; Woszczyk, Dariusz; Michalak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2026)
Chronic lymphocytic leukaemia (CLL) is a chronic lymphoproliferative disease characterized by the proliferation of monoclonal B lymphocytes. It is the most common adult leukaemia in Western populations. Chronic lymphocytic leukaemia can progress to the accelerated phase and Richter transformation. Accelerated CLL (aCLL) is likely to reflect the biological state of CLL tumour cells characterized by high proliferation, resulting in an aggressive form of the disease and, consequently, a poor prognosis. Richter transformation represents an aggressive histological transformation from CLL, most often to a large B-cell lymphoma. It is characterized by chemoresistance and subsequent short survival. Therefore, appropriate diagnostic and therapeutic approaches are essential to detect and effectively treat the progression of the underlying disease promptly. While a variety of tools for CLL diagnosis are available, there is no gold standard in clinical practice. Therefore, the aim of this review was to synthesise the current knowledge regarding diagnostic tools for aCLL and compare their relative advantages and disadvantages, to identify the most clinically efficacious option.